A lectin produced by a Streptomyces species targets mammalian pancreatic acinar cells in mice and humans - Janine C. Quijano; Honoka Natsuyama; Alonso Tapia; Karine Bagramyan; Jose A. Ortiz; Jacob Mares; Markus Kalkum; Yoko Fujita-Yamaguchi; Hsun Teresa Ku (Scientific Reports, 2025)
Abstract Lectins are produced in almost all life forms, can interact with targets (glycans) in a cross-kingdom manner and have served as valuable tools for studying glycobiology. Previously, a bacterial lectin, named Streptomyces hemagglutinin (SHA), was found to agglutinate human type B erythrocytes. However, the binding of SHA to mammalian cell types other than human erythrocytes has not been explored. To address this, we produced a recombinant fusion protein, with the mCherry reporter protein proceeding the SHA protein (referred to as mCherry-SHA), and performed co-immunofluorescence staining analysis. We focused on the normal pancreas in this study because glycans on pancreatic cells have been associated with initiation and progression of pancreatic cancer, a deadly disease. We found that only acinar, but not ductal or endocrine cells were stained positively with mCherry-SHA from embryonic day (E) 18.5 to 35 weeks old mice; in contrast, E12.5 and E15.5 pancreas display minimal mCherry-SHA binding. In adult humans, mCherry-SHA also targeted acinar cells specifically; however, only tissue from blood type B donors, but not type A or O donors, showed positivity. Together, these results demonstrate that SHA can bind to normal murine and human pancreatic acinar cells and that SHA-binding glycans are developmentally regulated.